Potential Application of Essential Oils for Mitigation of Listeria monocytogenes in Meat and Poultry Products - Yousefi, Mojtaba; Khorshidian, Nasim; Hosseini, Hedayat (Frontiers in Nutrition, 2020)
One of the most important challenges in the food industry is to provide healthy and safe food. Therefore, it is not possible to achieve this without different processes and the use of various additives. In order to improve safety and extend the shelf life of food products, various synthetic preservatives have been widely utilized by the food industry to prevent growth of spoilage and pathogenic microorganisms. On the other hand, consumers' preference to consume food products with natural additives induced food industries to use natural-based preservatives in their production. It has been observed that herbal extracts and their essential oils could be potentially considered as a replacement for chemical antimicrobials. Antimicrobial properties of plant essential oils are derived from some main bioactive components such as phenolic acids, terpenes, aldehydes, and flavonoids that are present in essential oils. Various mechanisms such as changing the fatty acid profile and structure of cell membranes and increasing the cell permeability as well as affecting membrane proteins and inhibition of functional properties of the cell wall are effective in antimicrobial activity of essential oils. Therefore, our objective is to revise the effect of various essential oils and their bioactive components against Listeria monocytogenes in meat and poultry products.